PERAN PENYULUH AGAMA ISLAM DALAM PEMBINAAN KELUARGA MODERASI BERAGAMA DI DESA MATA ALLO KECAMATAN BONTOMARANNU KABUPATEN GOWA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2025)
Abstract: The main issue in this research is: "How is the role of Islamic Religious Counselors in the development of religiously moderate families in Mata Allo Village, Bontomarannu District, Gowa Regency?" The research questions are: (1) What are the programs of Islamic Religious Counselors in the development of religiously moderate families in Mata Allo Village, Bontomarannu District, Gowa Regency? (2) How successful are the Islamic Religious Counselors in developing religiously moderate families in Mata Allo Village, Bontomarannu District, Gowa Regency?. This research uses a descriptive qualitative method located in Mata Allo Village, Bontomarannu District, Gowa Regency, with a case study approach. The primary data sources in this research are Jabbar Tahuddin as the key informant, and ten assisted families from Mata Allo Village as additional informants. Secondary data sources include books, theses, journals, literature, and other supporting references. Data collection methods used are observation, interviews, and documentation. Data analysis was conducted in three stages: data reduction, data presentation, and conclusion drawing. The results of this research show that the role of Islamic Religious Counselors in fostering religiously moderate families in Mata Allo Village, Bontomarannu District, Gowa Regency is carried out through several programs: (1) Interfaith Dialogues for religious moderation in the religious moderation village of Mata Allo, Bontomarannu District; (2) Dissemination of religious moderation values in Mata Allo Village, Bontomarannu District; and (3) Inter- and intra-religious dialogues in Mata Allo Village, Bontomarannu District. The success of the Islamic Religious Counselors in this effort is marked by: (1) Families gaining an understanding of religious moderation; (2) Families showing tolerance and fairness; and (3) Families demonstrating self-control in practicing religion.